2007
DOI: 10.1038/sj.leu.2404696
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of recurring sites of uniparental disomy in follicular and transformed follicular lymphoma

Abstract: Single-nucleotide polymorphism (SNP) array analysis was performed using the 10K GeneChip array on a series of 26 paired follicular lymphoma (FL) and transformed-FL (t-FL) biopsies and the lymphoma cell lines SCI-1, DoHH2 and RL2261. Regions of acquired homozygosity were detected in 43/52 (83%) primary specimens with a mean of 1.7 and 3.0 aberrations in the FL and t-FL, respectively. A notable feature was the occurrence of recurring sites of acquired uniparental disomy (aUDP) on 6p, 9p, 12q and 17p in cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 45 publications
(56 reference statements)
2
54
2
Order By: Relevance
“…6,14,16,17 A region of copy-number loss on 1p frequently had aUPD in FL and tFL (supplemental Figure 3B). A previous study 16 found 1p36 aUPD to negatively correlate with OS; however, we did not observe this, nor was aUPD at TNFRSF14 predictive of OS (data not shown).…”
Section: Acquired Uniparental Disomymentioning
confidence: 99%
“…6,14,16,17 A region of copy-number loss on 1p frequently had aUPD in FL and tFL (supplemental Figure 3B). A previous study 16 found 1p36 aUPD to negatively correlate with OS; however, we did not observe this, nor was aUPD at TNFRSF14 predictive of OS (data not shown).…”
Section: Acquired Uniparental Disomymentioning
confidence: 99%
“…23 UPD is considered to be one of the genetic mechanisms involved in tumor suppressor inactivation as mutated or deleted alleles of tumor suppressors could become homozygous through mitotic recombination. [75][76][77][78] Interestingly, studies of UPD in MPN and other myeloid malignancies showed that UPD is often involved in oncogene amplification. Semi-dominant oncogenic mutations present in neoplastic tissues in a heterozygous state can become homozygous due to mitotic recombination.…”
Section: Upd and Variability Of Mutational Burden In Mpnmentioning
confidence: 99%
“…Transformation occurs by clonal evolution from a common mutated precursor, as shown by sequencing of rearranged VDJ sequences, 15 or whole exomes or genomes. 13,16 Recurrent genetic alterations that evolve during the process of transformation include: CDKN2A deletions and/or loss of heterozygosity 13,17 ; translocations, gains, amplifications, or mutations involving MYC 13,18,19 ; mutations, deletions, and loss of heterozygosity affecting TP53 13,[20][21][22][23][24] ; and mutations or deletions of B2M and CD58. 13 Increased proliferation resulting from cell cycle deregulation, defective DNA damage response, and escape from immune surveillance therefore emerge as critical elements of histologic progression of FL to an aggressive lymphoma.…”
Section: Introductionmentioning
confidence: 99%